Ultrafine Dual‐Phased Carbide Nanocrystals Confined in Porous Nitrogen‐Doped Carbon Dodecahedrons for Efficient Hydrogen Evolution Reaction - Lu, Xue Feng; Yu, Le; Zhang, Jintao; Lou, Xiong Wen (David) (Advanced materials (Weinheim), 2019)
Designing novel non‐noble electrocatalysts with controlled structures and composition remains a great challenge for efficient hydrogen evolution reaction (HER). Herein, a rational synthesis of ultrafine carbide nanocrystals confined in porous nitrogen‐doped carbon dodecahedrons (PNCDs) by annealing functional zeolitic imidazolate framework (ZIF‐8) with molybdate or tungstate is reported. By controlling the substitution amount of MO4 units (M = Mo or W) in the ZIF‐8 framework, dual‐phase carbide nanocrystals confined in PNCDs (denoted as MC‐M2C/PNCDs) can be obtained, which exhibit superior activity toward the HER to the single‐phased MC/PNCDs and M2C/PNCDs. The evenly distributed ultrafine nanocrystals favor the exposure of active sites. PNCDs as the support facilitate charge transfer and protect the nanocrystals from aggregation during the HER process. Moreover, the strong coupling interactions between MC and M2C provide beneficial sites for both water dissociation and hydrogen desorption. This work highlights a new feasible strategy to explore efficient electrocatalysts via engineering on nanostructure and composition. Dual‐phased carbide nanocrystals consisting of MC and M2C (M = Mo or W) are realized through controlling the amount of MO4 units substituted in a framework of ZIF‐8. Owing to the desired composition and ultrafine structures, the dual‐phased MC‐M2C/PNCDs exhibit better catalytic performances toward the hydrogen evolution reaction than single‐phased MC/PNCDs and M2C/PNCDs.